The image of the Kurdish in the poem (There is no Kurdish but the wind) by (Mahmoud Darwish) - Fattah, Ali (Al-Adab Journal, 2024)
The poem deals with multiple images of the Kurdish individual, starting with the image of the desperate, displaced, and stranger Kurdish, up to the creative Kurdish who compensated for his absence with his creative texts, and his metaphorical language in which he excels over other of his peers, and ending with the image of the Kurdish martyr and his secret funeral, his call to the Kurdish uprising through the next generations, and his refusal to acquiesce. to the majeure circumstances that surround him. All this through a metaphorical language, correspondence with the senses, and the use of symbolic and other images derived from nature and moving images, which take colors as a ride to clarify the poetic goals and intents. The poem is characterized by an honest poetic experience that pushes the researcher to question the secret of this deep sincerity in feelings by an Arab poet writing about a Kurdish individual. The fighting brothers, and it contains references to the creative individual in whom the researcher finds a common denominator between the poet himself and Salim Barakat al-Kurdi, who was gifted this poem by Darwish.